Caution for using ventilatory frequency as an indicator of stress in fish - Barreto, R. E.; Volpato, G. L. (Elsevier B.V., 2004)
This study tested the use of ventilatory frequency (VF) as an indicator of stress in the Nile tilapia, Oreochromis niloticus (L.). Firstly, we tested the relationship between VF and plasma cortisol after confinement. Confined fish showed higher VF and plasma cortisol levels, but the latter continued to increase significantly for longer time than VF. Secondly, we conducted another experiment to test the use of VF as indicator of fish stress. In four out of six treatment, we confined the fish for different intervals (30 s, 5, 15 or 30 min). The others were used as control. In one, no handling was imposed. The other control consisted of introducing the partition (the same used to perform the confinement) into the aquarium for less than 4 s, without confinement and immediately removing the partition (partition control). Ventilatory frequency was increased for the partition control as much as for the longer duration of confinement. This clearly indicates that VF is a very sensitivity response to disturbance, but of limited use because this parameter does not reflect the severity of the stimulus. Thus, although VF is a non-invasive technique that does not require sophisticated recording equipment, its usefulness is limited. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: stress; ventilatory frequency; cortisol; confinement; Nile filapia; fish